Requirements engineering for software and systems - Laplante, Phillip A. (Applied software engineering series, 2014)
"Solid requirements engineering has increasingly been recognized as the key to improved, on-time and on-budget delivery of software and systems projects. This book provides practical teaching for graduate and professional systems and software engineers. It uses extensive case studies and exercises to help students grasp concepts and techniques. With a focus on software-intensive systems, this text provides a probing and comprehensive review of recent developments in intelligent systems, soft computing techniques, and their diverse applications in manufacturing. The second edition contains 100% revised content and approximately 30% new material"--